A threefold interpenetrated two‐dimensional zinc(II) supramolecular architecture based on 3‐nitrobenzoic acid and 4, 4′‐bipyridine. Issue 2 (19th January 2016) - Tang, Long; Wang, Ji-Jiang; Fu, Feng; Wang, Sheng-Wen; Liu, Qi-Rui
Abstract : Zn II ions are connected by 4, 4′‐bipyridine ligands to form a one‐dimensional zigzag chain and the chains are decorated with anionic 3‐nitrobenzoate ligands which interact further through aromatic π–π stacking interactions, expanding the structure into a threefold interpenetrated two‐dimensional supramolecular architecture. Abstract : With regard to crystal engineering, building block or modular assembly methodologies have shown great success in the design and construction of metal–organic coordination polymers. The critical factor for the construction of coordination polymers is the rational choice of the organic building blocks and the metal centre. The reaction of Zn(OAc)2 ·2H2 O (OAc is acetate) with 3‐nitrobenzoic acid (HNBA) and 4, 4′‐bipyridine (4, 4′‐bipy) under hydrothermal conditions produced a two‐dimensional zinc(II) supramolecular architecture, catena ‐poly[[bis(3‐nitrobenzoato‐κ 2 O, O ′)zinc(II)]‐μ‐4, 4′‐bipyridine‐κ 2 N : N ′], [Zn(C7 H4 NO4 )2 (C10 H8 N2 )] n or [Zn(NBA)2 (4, 4′‐bipy)] n, which was characterized by elemental analysis, IR spectroscopy, thermogravimetric analysis and single‐crystal X‐ray diffraction analysis. The Zn II ions are connected by the 4, 4′‐bipy ligands to form a one‐dimensional zigzag chain and the chains are decorated with anionic NBA ligands which interact further through aromatic π–π stacking interactions, expanding the structure into a threefold interpenetrated two‐dimensional supramolecular architecture. The solid‐state fluorescence analysis indicates a slight blue shift compared with pure 4, 4′‐bipyridine and HNBA.